Effects of the isostretching method on morphological parameters and on a set of motor tests in the elderly - Christina Cruz Cepeda; Andre Félix Rodacki; Leslie Nathan Persch; Peterson Pereira Silva; Silvia Buba; Vanessa Freitas Dressler (Universidade Federal de Santa Catarina, 2013)
Moderate intensity resistance training seems to be effective in providing significant improvements on strength, balance and function in the elderly. This study aimed to analyze the effect of a 12-week isostretching training on functional capacity and muscle architecture in elderly women. The sample included 25 volunteers (n = 25) divided into a control group (CG, n = 11, 62.3 ± 1.9 years old, 1.58 ± 0.06 m, 73.4 ± 1.4 kg) that followed their physical activity habits and an experimental group (EG, n = 14, 64.2 ± 4.3 years, 1.56 ± 0.05 m, 74.2 ± 1.6 kg) that was submitted to an isostretching program. The following assessments were used: Timed Up and Go-TUGT, Tinetti balance test and evaluation of morphological parameters through ultrasound imaging technique. The results showed that the EG improved (p <0.05) in both TUGT and Tinetti. In the morphologic parameters of the vastus lateralis muscle in the EG, we observed the following: mean increase of 3.6 mm in length issue relaxation (p <0.05, ES = 1.15); increase of 4.9 mm in isometric contraction (p <0.05; ES = 1.94); increase of 16% in the pennation angle in the relaxed condition (p <0.05; ES = 0.70); increase of 12% in isometric contraction (p <0.05; ES = 0.50); increase of 8% in thickness in the relaxed condition (p <0.05, EF = 0.52); and increase of 9% in isometric contraction (p <0.05, EF = 0.43). The GC did not show any significant changes. The isometric training through the isostretching method promoted changes in the morphological and muscle parameters and also improved the functional abilities in elderly women.